Collaboration as a co-creation strategy to create a market niche in the media industry - Zarkasi, Irwa Rochimah; Kulau, Febriansyah; Karolina, Cut Meutia; Intana, Lila (Jurnal Komunikasi, 2025)
Technological changes and the pandemic have significantly disrupted the media industry. This situation forces media companies to make changes in order to survive. Using a qualitative approach, this research tries to reveal the innovations made by media companies, especially groups that started from print media, namely national media (Bisnis Indonesia Group) and regional media (Radar Cirebon Group). Using the concept of co-creation, this research reveals media innovation strategies to survive and adapt to environmental changes. The innovation carried out by the two media is to collaborate with various parties. Community empowerment is a form of collaboration, in addition to creating new business units, making content changes, and targeting young audiences as a widening of the reader segment. This innovation has proven to have a positive impact on the lives of media organizations. This research can be a lesson for media companies that are still looking for a formula for managing media businesses.